2022
DOI: 10.1002/smtd.202201251
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Advanced Triboelectric Materials for Energy Harvesting and Emerging Applications

Abstract: The properties of materials play a significant role in triboelectric nanogenerators (TENGs). Advanced triboelectric materials for TENGs have attracted tremendous attention because of their superior advantages (e.g., high specific surface area, high porosity, and customizable macrostructure). These advanced materials can be extensively applied in numerous fields, including energy harvester, wearable electronics, filtration, and self‐powered sensors. Hence, designing triboelectric materials as advanced functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 281 publications
0
9
0
Order By: Relevance
“…Hence, careful selection of appropriate materials and assembly structures is critical to ensure optimal performance in the development of triboelectric sensors. In general, the electrospun micro/nanofibers are endowed with a high flexibility, good wearing comfort, and large specific surface area, rendering them as highly suitable charge generation layers in the preparation of triboelectric sensors . Plus, the morphology of electrospun micro/nanofibers can be effectively adjusted through controlling electrospinning processing parameters, thereby accordingly regulating the frictional electrical output and mechanical sensing performance of the triboelectric sensor made of electrospun nanofibrous membranes .…”
Section: Design Of Electrospun Flexible Biomechanical Sensorsmentioning
confidence: 99%
“…Hence, careful selection of appropriate materials and assembly structures is critical to ensure optimal performance in the development of triboelectric sensors. In general, the electrospun micro/nanofibers are endowed with a high flexibility, good wearing comfort, and large specific surface area, rendering them as highly suitable charge generation layers in the preparation of triboelectric sensors . Plus, the morphology of electrospun micro/nanofibers can be effectively adjusted through controlling electrospinning processing parameters, thereby accordingly regulating the frictional electrical output and mechanical sensing performance of the triboelectric sensor made of electrospun nanofibrous membranes .…”
Section: Design Of Electrospun Flexible Biomechanical Sensorsmentioning
confidence: 99%
“…Besides improving the dielectric property of the friction layer, optimizing the structure design of the friction layer can enhance the effectual contact area of the friction layer and improve the charge density. , To date, many endeavors have been made to increase the triboelectric charge density of the friction layer by forming various micro/nano-scale patterns using physical surface modification, including templating, three-dimensional printing (3DP), etching, electrospinning (ES), etc. , ES is one of the simplest and low-cost methods to prepare continuous and uniform micro/nanofibers. Micro/nanofiber membranes have good potential in the preparation of novel friction layers due to their advantages of large specific surface area, breathability, high porosity, large accumulated surface charge density, flexibility, and lightweight. , Compared to other methods, the ES technique can simply control the dipole moment of certain polymers by arranging them at the molecular level or adjusting their crystal structure to obtain higher electrical outputs. , Sriphan et al also found that the electrospun barium titanate (BT) fibers had higher crystallinity than BT powder. Furthermore, electrospun nanofibers can reduce the adhesion between the two friction layers and improve durability .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, electrospun nanofibers can reduce the adhesion between the two friction layers and improve durability . By adjusting spinning parameters, such as spinning solution, spinning nozzle structure, and collector unit, beaded, porous, core–shell, aligned nanofibers, and nanofiber yarns can be easily obtained. , Among them, nanofibers with porous structure and beaded structure have higher specific surface area and surface roughness than conventional micro/nanofibers, which can promote the surface charge density and have a great potential in fabricating high-performance TENGs …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations